Ikindene hekugu: uma etnografia da luta e dos lutadores no Alto Xingu - Costa, Carlos Eduardo (2013)
This research aims to explore the anthropological debate on sportive practices through the description and analysis of dispute modes in different contexts. In the literature of sportive practices anthropology, football has frequently been used as a framework for research into indigenous societies; expanding on these theoretical models developed for football allows for greater understanding into the rituals within the society to which they belong, and to highlight the relationship between football and other practices. The ethnographic study proposes the Upper Xingu from researches conducted with the Kalapalo peoples of Tanguro village, hence the emphasis on wrestling in Alto Xingu (kal. ikindene). Anthropological themes highlighted on the peoples of the region, such as the construction of the body, chieftaincy, complex inter-ethnic rituals and mythology are directly linked to the wrestling. The objectives also include a more positive assessment for what was termed as "sportive practices" within indigenous societies, ethnographically in the Upper Xingu. This is not only to realize the "sportive" nature of these activities, but above all to understand the symbolic space for each mode, whether in the village, or in rituals disputes that renegotiate the dynamics of alliances and rivalries in this regional complex.